A comparison of molecular typing methods for Moraxella catarrhalis - Pingault, N.; Lehmann, Deborah; Bowman, J.; Riley, T. (Blackwell Science Ltd, 2007)
* Skip to main content Blackwell Synergy Email: ? Password: University of Western Australia Library * Register * Forgotten Password * Athens/Institution Login * Synergy Home | * Browse | * Search | * My Synergy | * Books Online | * Resources | o For Librarians o For Authors o For Societies o For Press * About | * Help Journal Menu * Table of Contents * List of Issues Tools * Email this article * Add to favorite articles * Export this citation * Alert me when this article is cited: Email | RSS (What is this?) * View ISI citation * Related articles Publication history Published article online: 11 Sep 2007 Issue online: 27 Nov 2007 2007/1064: received 24 July 2006, revised 21 May 2007 and accepted 24 May 2007 * Home > * List of Issues > * Table of Contents > * Article Abstract Journal of Applied Microbiology Journal of Applied Microbiology Volume 103 Issue 6 Page 2489-2495, December 2007 To cite this article: N.M. Pingault, D. Lehmann, J. Bowman, T.V. Riley (2007) A comparison of molecular typing methods for Moraxella catarrhalis Journal of Applied Microbiology 103 (6) , 2489–2495 doi:10.1111/j.1365-2672.2007.03536.x Prev Article Next Article You have full access rights to this content Abstract ORIGINAL ARTICLE A comparison of molecular typing methods for Moraxella catarrhalis * N.M. Pingault11 School of Biomedical, Biomolecular and Chemical Sciences, The University of Western Australia, Perth, WA, Australia, * D. Lehmann2,32 Telethon Institute for Child Health Research, Perth, WA, Australia3 Centre for Child Health Research, The University of Western Australia, Perth, WA, Australia, * J. Bowman44 PathWest Laboratory Medicine WA, Perth, WA, Australia and * T.V. Riley1,41 School of Biomedical, Biomolecular and Chemical Sciences, The University of Western Australia, Perth, WA, Australia4 PathWest Laboratory Medicine WA, Perth, WA, Australia * 1 School of Biomedical, Biomolecular and Chemical Sciences, The University of Western Australia, Perth, WA, Australia 2 Telethon Institute for Child Health Research, Perth, WA, Australia 3 Centre for Child Health Research, The University of Western Australia, Perth, WA, Australia 4 PathWest Laboratory Medicine WA, Perth, WA, Australia Thomas V. Riley, Locked Bag 2009, Nedlands, WA 6909, Australia. E-mail: triley@cyllene.uwa.edu.au Abstract Aims: Three molecular typing techniques were examined to determine which method was the most discriminatory in order to perform epidemiological typing of Moraxella catarrhalis. Methods and Results: Twenty-five Mor. catarrhalis isolates obtained from nasopharyngeal aspirates collected from Aboriginal and non-Aboriginal children were subjected to random amplified polymorphic DNA (RAPD) analysis, automated ribotyping and pulsed field gel electrophoresis (PFGE). RAPD analysis determined two Mor. catarrhalis types, automated ribotyping with PstI determined four Mor. catarrhalis ribogroups and PFGE analysis with NotI determined 21 pulse field groups within the 25 isolates examined. Conclusions: Analysis of discrimination index and typeability demonstrated that PFGE is the most discriminatory method for typing Mor. catarrhalis. Significance and Impact of the Study: This study confirms that PFGE is the most appropriate molecular tool for the epidemiological study of Mor. catarrhalis. Users who read this article also read: Arsenic-resistant bacteria isolated from contaminated sediments of the Orbetello Lagoon, Italy, and their characterization M. Pepi, M. Volterrani, M. Renzi, M. Marvasi, S. Gasperini, E. Franchi and S.E. Focardi Journal of Applied Microbiology, Volume 103, Issue 6, Page 2299-2308, Dec 2007, doi: 10.1111/j.1365-2672.2007.03471.x * Abstract * | References * | Full Text HTML * | Full Text PDF (325 KB) OpenURL University of Western Australia - Crawley - AUS Occurrence and levels of indicators and selected pathogens in different sludges and biosolids C. Guzmán, J. Jofre, M. Montemayor and F. Lucena Journal of Applied Microbiology, Volume 103, Issue 6, Page 2420-2429, Dec 2007, doi: 10.1111/j.1365-2672.2007.03487.x * Abstract * | References * | Full Text HTML * | Full Text PDF (128 KB) OpenURL University of Western Australia - Crawley - AUS Oil-utilizing bacteria associated with fish from the Arabian Gulf S.S. Radwan, R.H. Al-Hasan, H.M. Mahmoud and M. Eliyas Journal of Applied Microbiology, Volume 103, Issue 6, Page 2160-2167, Dec 2007, doi: 10.1111/j.1365-2672.2007.03454.x * Abstract * | References * | Full Text HTML * | Full Text PDF (256 KB) OpenURL University of Western Australia - Crawley - AUS Diversity and antimicrobial susceptibility of oxytetracycline-resistant isolates of Stenotrophomonas sp. and Serratia sp. associated with Costa Rican crops C. Rodríguez, A. Wachlin, K. Altendorf, F. García and A. Lipski Journal of Applied Microbiology, Volume 103, Issue 6, Page 2550-2560, Dec 2007, doi: 10.1111/j.1365-2672.2007.03496.x * Abstract * | References * | Full Text HTML * | Full Text PDF (276 KB) OpenURL University of Western Australia - Crawley - AUS Diagnosis of Xanthomonas axonopodis pv. citri, causal agent of citrus canker, in commercial fruits by isolation and PCR-based methods M. Golmohammadi, J. Cubero, J. Peñalver, J.M. Quesada, M.M. López and P. Llop Journal of Applied Microbiology, Volume 103, Issue 6, Page 2309-2315, Dec 2007, doi: 10.1111/j.1365-2672.2007.03484.x * Abstract * | References * | Full Text HTML * | Full Text PDF (149 KB) OpenURL University of Western Australia - Crawley - AUS Two different PCR approaches for universal diagnosis of brown rot and identification of Monilinia spp. in stone fruit trees I. Gell, J. Cubero and P. Melgarejo Journal of Applied Microbiology, Volume 103, Issue 6, Page 2629-2637, Dec 2007, doi: 10.1111/j.1365-2672.2007.03495.x * Abstract * | References * | Full Text HTML * | Full Text PDF (228 KB) OpenURL University of Western Australia - Crawley - AUS This Article * Abstract * References * Full Text HTML * Full Text PDF (242 KB) * Rights & Permissions Search In SynergyPubMed (MEDLINE)CrossRef By keywords automated ribotypingmolecular typingMor. catarrhalispulsed field gel electrophoresisrandom amplified polymorphic DNA By author N.M. PingaultD. LehmannJ. BowmanT.V. Riley * Privacy Statement | * Terms & Conditions | * Contact | * Help Blackwell Publishing Blackwell Synergy® is a Blackwell Publishing, Inc. registered trademark Partner of CrossRef, COUNTER, AGORA, HINARI and OARE Technology Partner — Atypon Systems, Inc.